Stability and oscillations in spatially-extended models of population interaction - Nelli A. Ajabyan (Изд-во НАН РА)
Conditions for species coexistence in a simple patch-occupancy metapopulation model are derived. The model is described by a system of ordinary differential equations. The ecological stability of the community is interpreted in terms of conservation of species composition in the model. The limits for the stability are related to the boundness of the model solutions in phase space. Analytical results show that there are regions in the parameter space where the species coexistence can occur depending on characteristics of competing species interaction and structure of the links connecting isolated patches.
Keywords: Mathematics